Dual Language Competencies of Turkish–German Children Growing Up in Germany: Factors Supportive of Functioning Dual Language Development - Ertanir, Beyhan; Kratzmann, Jens; Frank, Maren; Jahreiss, Samuel; Sachse, Steffi (Frontiers in Psychology, 2018)
This paper is about the first (L1) and second language (L2) skills of Turkish-German dual language learners (DLLs), the interrelatedness of the L1 and L2 skills, and their relation to other selected child and family variables. The first aim of the study was to examine L1 and L2 performance and the relation between the languages. Second, the study sought to explore the conditions in which functioning dual language development can be achieved, while trying to predict the extent to which child and environmental factors are related to the DLLs’ language competencies. L1 and L2 language skills of N = 69 bilingually developing 3- to 5-year-old Turkish-German children were assessed via standardized tests. In addition, information on the children’s sociodemographic variables and home language environments was obtained by means of parental questionnaires. Correlational analyses were used to examine the interrelations between L1 and L2 skills and multiple regression analyses were conducted in order to predict the children’s language competencies. The children showed age-appropriate language skills in L1 (Turkish) and lower language skills in L2 (German). Whereas their phonological memory abilities were positively correlated with L1 and L2 skills, their expressive vocabulary in L1 was negatively correlated with L2 skills. Our findings also indicated that phonological memory was a strong predictor of language abilities. Concerning family variables, both early daycare entry and stimulating home language environment were significant predictors of better L2 skills. Lastly, balanced use of both languages at home had no negative consequences on language competencies. Although more research is needed, this study shows the benefits of using a combined language measure including both L1 and L2 skills to predict DLLs’ language competencies without disregarding either of their languages.